Nutritional and bioactive compounds of Amaranthus spp. in Brazil (Research, Society and Development, 2022)
The objective of this research was to evaluate the physicochemical characteristics of Amaranthus spp. commonly happening in Brazil, besides defining the efficiency of different extraction processes of the phenolic compounds and of the antioxidant activity. Five species of the genus Amaranthus (A. spinosus, A. viridis, A. retroflexus, A. hybridus var. paniculatus e A. deflexus) were evaluated in regard to their physicochemical characteristics such as vitamin C, soluble solids, pH, moisture, lipids and protein levels as well as the coloration of the leaves. Also, the phenolic compounds and the antioxidants were defined through four extraction processes (reflux; hydroalcoholic turbo-extraction; aqueous; and methanolic). The species A. spinosus has stood out for its vitamin C levels, pH and moisture, indicating the potential of the species when compared to the others. The leaf extracts of the five Amaranthus species present differences in the total phenol levels, flavonoids and hydro flavonoids when subject to different extraction methods. The antioxidant activities were favored by the reflux and hydroalcoholic turbo-extraction, with A. viridis standing out in the reflux methods and A. spinosus in the hydroalcoholic.